P2_3 A Tapered Tower - Anand, Jasdeep; Buccheri, Alex; Gorley, Michael; Weaver, Iain (Physics Special Topics, 2009)
<span style="font-size: 10pt; font-family: ";Calibri";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">This paper evaluates the possibility of building a space elevator from a mechanical standpoint; calculating the yield stress and required density of a homogeneous material that such a structure would ideally need. It is concluded that a tapered tower made from carbon nanotubes may potentially be feasible.